Method for manufacturing active material layer for battery, active material layer for battery, and battery
By using nanosecond pulsed laser on the active material layer of the battery, the problem of reducing active material and insufficient permeability of the electrolyte is solved, and the battery capacity and resistance are retained are achieved.
Patent Information
- Application Number
- CN202411203923.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-08
- Filing Date
- 2024-08-30
- Publication Date
- 2025-03-11
AI Technical Summary
In a battery using a nonaqueous electrolyte, when a region with less adhesive is formed by laser irradiation, the active substance may be removed, resulting in a decrease in the battery capacity. At the same time, the electrolyte is insufficient to impregnate the active substance layer, thereby increasing the battery resistance.
The active material layer is subjected to local irradiation by using nanosecond pulse laser, and the input heat is controlled to be above 0.005J/mm2 and below 0.050J/mm2 to ensure hot melting and cohesion of the adhesive, enhancing the permeability of the electrolyte, and suppressing mass loss of the active material.
It effectively suppresses the reduction of battery capacity, reduces the battery resistance, and improves the overall performance of the battery.
Smart Images

Figure BDA0005018487400000101 
Figure HDA0005018487410000011 
Figure HDA0005018487410000012
Abstract
Description
Technical Field
[0001] The present disclosure relates to a method for producing an active material layer for a battery, the active material layer for a battery, and a battery. Background Art
[0002] Conventionally, in liquid-based batteries using an electrolyte solution, an active material layer including a binder and an active material is used.
[0003] For example, Japanese Patent Gazette No. 2011-171020 discloses a non-aqueous electrolyte battery, which includes an electrode group, an outer packaging material and a non-aqueous electrolyte, the electrode group has a positive electrode, a negative electrode and a separator, the positive electrode has a positive electrode collector, and a positive electrode layer containing a positive electrode active material and a binder and formed on the positive electrode collector, the negative electrode has a negative electrode collector, and a negative electrode layer containing a negative electrode active material and a binder and formed on the negative electrode collector, the separator is interposed between the positive electrode layer and the negative electrode layer, and is wound together with the positive electrode and the negative electrode, at least one of the positive electrode layer and the negative electrode layer has a plurality of penetration promotion portions, the plurality of penetration promotion portions are formed on their respective surface sides to connect two long sides (S), the binder of the plurality of penetration promotion portions is less than the binder on the surface side of other regions (R), and the penetration of the non-aqueous electrolyte is promoted relative to the surface side of the region (R). Summary of the invention
[0004] Problems to be solved by the invention
[0005] Japanese Patent Publication No. 2011-171020 discloses a method of forming a region with less binder on the surface of an electrode layer of a battery using a non-aqueous electrolyte using a CW laser. However, sometimes, active materials and the like are removed from the electrode layer by laser irradiation, and the active materials are reduced, resulting in a decrease in the battery capacity of the battery.
[0006] In addition, in a battery, the permeability of the electrolyte solution into the active material layer affects the resistance of the battery. Therefore, it is desirable to reduce the resistance of the battery by improving the permeability of the electrolyte solution into the active material layer.
[0007] The present disclosure has been made in view of the above-mentioned actual situation, and an object of the present disclosure is to provide a method for manufacturing a battery active material layer capable of reducing battery resistance while suppressing a decrease in battery capacity in the battery, a battery active material layer, and a battery having the battery active material layer.
[0008] Means for solving problems
[0009] Means for solving the above-mentioned problems include the following.
[0010] <1> A method for producing an active material layer for a battery, comprising: preparing an active material layer including a binder and an active material; and applying heat of 0.005 J / mm 2 Above and 0.050J / mm 2 The irradiation step of nanosecond pulse laser was performed under the following conditions.
[0011] <2> The method for producing a battery active material layer according to <1>, wherein the irradiation step is a step of irradiating with nanosecond pulse laser light under conditions of an output of 1.25 W to 5 W and an overlap rate of 0% to 63%.
[0012] <3> A battery active material layer comprising a binder and an active material, wherein an average particle size of the binder in a surface image based on EPMA mapping obtained by dyeing the binder is larger than an average particle size of the binder in an image of a cross section at a depth of 20 μm based on EPMA mapping.
[0013] <4> A battery active material layer comprising a binder and an active material, wherein an average particle size of the binder in a surface image obtained by EPMA mapping in which the binder is dyed is 30 μm or more.
[0014] <5> A battery comprising the battery active material layer according to <3> or <4> as at least one of a positive electrode active material layer and a negative electrode active material layer.
[0015] Effects of the Invention
[0016] According to the present disclosure, a method for producing a battery active material layer capable of reducing battery resistance while suppressing a decrease in battery capacity in a battery, a battery active material layer, and a battery having the battery active material layer can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a graph showing the results of measuring the change in mass (mass loss (%)) of the active material layer before and after nanosecond pulse laser irradiation in Examples and Comparative Examples.
[0018] Figure 2 It is a graph showing the results of measuring the battery resistance in Examples and Reference Examples. DETAILED DESCRIPTION
[0019] Hereinafter, an embodiment as an example of the present disclosure will be described. These descriptions and examples illustrate the embodiment, but do not limit the scope of the invention.
[0020] In the numerical range recorded in stages in this specification, the upper limit or lower limit recorded in one numerical range can be replaced by the upper limit or lower limit of other numerical ranges recorded in stages. In addition, in the numerical range recorded in this specification, the upper limit or lower limit of its numerical range can be replaced by the value shown in the embodiment.
[0021] Each component may contain a plurality of substances corresponding to the component.
[0022] When referring to the amount of each component in a composition, if there are a plurality of substances corresponding to each component in the composition, unless otherwise specified, it means the total amount of the plurality of substances present in the composition.
[0023] The term "process" does not only refer to an independent process, but also includes a process that cannot be clearly distinguished from other processes as long as the expected effect of the process is achieved.
[0024] <Method for producing active material layer for battery>
[0025] The method for producing an active material layer for a battery according to an embodiment of the present disclosure comprises: preparing an active material layer including a binder and an active material; and applying heat of 0.005 J / mm 2 Above and 0.050J / mm 2 The irradiation step of nanosecond pulse laser was performed under the following conditions.
[0026] In the method for producing a battery active material layer according to an embodiment of the present disclosure, heat is locally applied to the surface of the active material layer using nanosecond pulse laser, and at this time, 0.005 J / mm 2 The above input heat (input heat). Therefore, the binder on the surface of the active material layer is thermally melted and condensed (aggregated). Thus, the reaction surface at the surface of the active material layer is ensured, and the penetration path of the electrolyte into the active material layer is ensured, and as a result, the resistance of the battery having the active material layer can be reduced.
[0027] In addition, nanosecond pulse laser was used as the laser irradiated to the surface of the active material layer, and the input heat during the irradiation of the nanosecond pulse laser was controlled to 0.050 J / mm 2 That is, while locally applying heat to the surface of the active material layer using nanosecond pulse laser, the total heat is suppressed. Thus, the active material is suppressed from being removed from the active material layer due to laser irradiation, the mass loss of the active material is suppressed, and thus the reduction in battery capacity in the battery including the active material layer is suppressed.
[0028] Furthermore, by using nanosecond pulse laser as the laser beam irradiated onto the surface of the active material layer, removal of the binder from the active material layer is suppressed, thereby maintaining the adhesive force in the active material layer and suppressing generation of foreign matter from the active material layer.
[0029] Hereinafter, each step of the method for producing the battery active material layer according to the embodiment of the present disclosure will be described.
[0030] - Step of preparing active material layer -
[0031] The method for producing an active material layer for a battery according to an embodiment of the present disclosure includes a step of preparing an active material layer including a binder and an active material.
[0032] Furthermore, as the active material layer, both the negative electrode active material layer and the positive electrode active material layer can be used. The negative electrode active material layer and the positive electrode active material layer can be formed by a conventionally known method. For example, they can be formed by applying a solution containing a raw material of the active material layer and drying it.
[0033] The following describes the active material, the binder, and the like separately for the negative electrode active material layer and the positive electrode active material layer.
[0034] Negative electrode active material layer
[0035] Examples of the negative electrode active material include graphite-based carbon such as natural graphite, artificial graphite, and amorphous coated graphite. The proportion of graphite in the graphite-based carbon is about 50% by mass or more, preferably 80% by mass or more.
[0036] Examples of the binder contained in the negative electrode active material include rubbers such as styrene butadiene copolymer (SBR) and halogenated vinyl resins such as polyvinylidene fluoride (PVdF).
[0037] The negative electrode active material layer may further contain other components, for example, a thickener, etc. Examples of the thickener include celluloses such as carboxymethyl cellulose (CMC).
[0038] Positive electrode active material layer
[0039] Examples of positive electrode active materials include lithium nickel cobalt manganese composite oxides (hereinafter sometimes simply referred to as "LNCM"). The simplest LNCM has the following general formula: LiNi x Co y Mn zO2 (wherein x, y, z are 0<x<1, 0<y<1, 0<z<1, x+y+z=1.) In addition to Li, Ni, Co, and Mn, LNCM may contain other added elements, such as transition metal elements other than Ni, Co, and Mn, and typical metal elements other than Li. LNCM has a layered crystal structure. LNCM accounts for more than 50% by mass of the entire positive electrode active material, for example, 80 to 100% by mass. The positive electrode active material may be composed only of LNCM.
[0040] Examples of other positive electrode active materials include lithium nickel composite oxides, lithium cobalt composite oxides, and lithium nickel manganese composite oxides.
[0041] Examples of the binder contained in the positive electrode active material layer include vinyl halide resins such as polyvinylidene fluoride (PVdF).
[0042] The positive electrode active material layer may further contain other components, for example, a conductive material, etc. Examples of the conductive material include hardly graphitizable carbon, graphitizable carbon such as carbon black, and graphite.
[0043] -Irradiation process-
[0044] Next, in the irradiation step, the active material layer is heated to 0.005 J / mm 2 Above and 0.050J / mm 2 Nanosecond pulse laser was irradiated under the following conditions.
[0045] The nanosecond pulse laser refers to a pulse laser having a pulse width of 1 ns to 500 ns. The nanosecond pulse laser preferably has a pulse width of 1 ns to 100 ns.
[0046] Heat input
[0047] The nanosecond pulse laser irradiated to the active material layer in the irradiation step was set to input heat of 0.005 J / mm 2 Above and 0.050J / mm 2 the following.
[0048] The heat input is 0.005J / mm 2 As described above, the binder on the surface of the active material layer is melted and condensed by heat, which can ensure the penetration path of the electrolyte into the active material layer, thereby reducing the resistance of the battery including the active material layer. 2 Next, the active material is suppressed from being removed from the active material layer due to laser irradiation, and the battery capacity of the battery including the active material layer is suppressed from decreasing.
[0049] The lower limit of the input heat is more preferably 0.010 J / mm 2 More preferably, 0.015 J / mm 2 On the other hand, the upper limit of the input heat is more preferably 0.040 J / mm 2 Below, more preferably 0.030 J / mm 2 the following.
[0050] The amount of heat input from the nanosecond pulse laser can be controlled by adjusting the output power and the overlap ratio, for example.
[0051] Output power
[0052] From the viewpoint of suppressing the decrease in battery capacity in the battery and reducing battery resistance, the output power of the nanosecond pulse laser is preferably 1.25 W to 5.00 W, more preferably 1.50 W to 4.50 W, and even more preferably 2.00 W to 3.50 W.
[0053] Overlap rate
[0054] From the viewpoint of reducing the resistance of the battery while suppressing a decrease in battery capacity, the overlap ratio during irradiation with nanosecond pulse laser light is preferably 0% to 63%, more preferably 0% to 55%, and even more preferably 0% to 30%.
[0055] Here, the overlap ratio refers to the ratio of the area of the region repeatedly irradiated with the nanosecond pulse laser, and is represented by the following formula.
[0056] Formula: (area where laser is repeatedly irradiated) / ((area where laser is repeatedly irradiated)+(area where laser is not repeatedly irradiated))
[0057] Nanosecond pulse laser is a short pulse laser with a pulse width of nanosecond level. By repeatedly irradiating for a short time while moving the irradiation position of the laser a little bit, the entire area to be irradiated is irradiated with laser. The so-called area of repeated laser irradiation refers to the area that is repeatedly irradiated with laser as the last irradiation area because the movement of the irradiation position is small during the laser irradiation repeatedly performed while moving the irradiation position. For example, in the case of repeated irradiation without moving the irradiation position at all, the overlap rate becomes 100%, and in the case of repeated irradiation by moving the irradiation position away from the area irradiated in one laser irradiation, the overlap rate becomes 0%. The overlap rate can be controlled by, for example, adjusting the moving distance when repeatedly performing laser irradiation.
[0058] <Battery active material layer>
[0059] -First active material layer-
[0060] The first embodiment of the present disclosure involves an active material layer for a battery (referred to as the "first active material layer") comprising a binder and an active material, wherein the average particle size of the binder in an image of a surface obtained by dyeing the binder using EPMA mapping is larger than the average particle size of the binder in an image of a cross section at a depth of 20 μm obtained using EPMA mapping.
[0061] The fact that the average particle size [A] of the binder on the surface of the active material layer is larger than the average particle size [B] of the binder at a cross section at a depth of 20 μm from the surface indicates that the binder is aggregated on the surface of the active material layer. Therefore, the reaction surface on the surface of the active material layer can be ensured, and the permeation path of the electrolyte into the active material layer can be ensured, and as a result, the resistance in the battery including the active material layer can be reduced.
[0062] The first active material layer can be obtained, for example, by using the above-described method for producing an active material layer for a battery according to the embodiment of the present disclosure.
[0063] -Second active material layer-
[0064] The battery active material layer according to the second embodiment of the present disclosure (abbreviated as “second active material layer”) includes a binder and an active material, and the average particle size of the binder in a surface image obtained by EPMA mapping obtained by dyeing the binder is 30 μm or more.
[0065] The average particle size [A] of the binder on the surface of the active material layer being as high as 30 μm or more indicates that the binder is aggregated on the surface of the active material layer. Therefore, the reaction surface on the surface of the active material layer can be ensured, and the permeation path of the electrolyte into the active material layer can be ensured, and as a result, the resistance in the battery including the active material layer can be reduced.
[0066] In the second active material layer, the average particle size [A] of the binder on the surface is 30 μm or more, preferably 40 μm or more, and more preferably 45 μm or more. The upper limit of the average particle size [A] of the binder is, for example, preferably 100 μm or less, and more preferably 70 μm or less.
[0067] The second active material layer can be obtained, for example, by using the above-described method for producing an active material layer for a battery according to the embodiment of the present disclosure.
[0068] Here, a method for measuring the average particle size [A] of the binder on the surface of the active material layer will be described.
[0069] First, the active material layer is dyed according to the binder contained (for example, osmium (Os) dyeing). Next, an EPMA (Electron Probe Micro Analysis) mapping image is obtained for the surface of the dyed active material layer. The brightness data of the top 10% with the highest brightness is calculated from the obtained mapping image, and the brightness data is set as a threshold value to perform a binarization process. From the binarized image, the particle size of the binder particles (the length of the longest part in the image of the binder particles that are the subject) is measured. This measurement is performed on 20 binder particles, and the arithmetic mean is set as the average particle size.
[0070] Furthermore, with regard to the measurement of the average particle size [B] of the binder at a depth of 20 μm from the surface, after exposing the cross section at a depth of 20 μm from the surface by cutting or other methods, the average particle size is determined in the same manner as the above-mentioned average particle size [A].
[0071] <Battery>
[0072] A battery according to an embodiment of the present disclosure includes the first active material layer or the second active material layer as at least one of a positive electrode active material layer and a negative electrode active material layer.
[0073] A battery has, for example, a negative electrode, a positive electrode, a separator, and an electrolyte.
[0074] (Electrolyte)
[0075] Solvent
[0076] The electrolytic solution contains a solvent (non-aqueous solvent) and an electrolyte.
[0077] Examples of the solvent (non-aqueous solvent) include N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium bis(fluorosulfonyl)imide (DEME), 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide (EMI), and 1-ethyl-2,3-dimethylimidazolium bis(fluorosulfonyl)imide (DEMI-FSI).
[0078] Electrolytes
[0079] As the electrolyte in the electrolytic solution, for example, Li salts can be cited. As the Li salts, lithium bis(fluorosulfonyl)imide (LiFSI), LiPF6 (lithium hexafluorophosphate), lithium tetrafluoroborate (LiBF4), Li[N(CF3SO2)2], etc. can be cited.
[0080] The amount of the electrolyte may be, for example, 1.0 to 2.0 mol / L, preferably 1.0 to 1.5 mol / L.
[0081] The electrolyte may contain various additives in addition to the solvent and the electrolyte, such as a thickener, a film-forming agent, a gas generator, etc. The electrolyte is typically a non-aqueous electrolyte that is liquid at room temperature (e.g., 25±10°C). The electrolyte is typically liquid in the battery's operating environment (e.g., a temperature environment of -20 to +60°C).
[0082] (negative electrode)
[0083] The negative electrode includes, for example, a negative electrode current collector and a negative electrode active material layer fixed on the negative electrode current collector. As the negative electrode current collector, a conductive member composed of a metal with good conductivity (such as copper) is suitable. As the negative electrode active material layer, for example, the above-mentioned first active material layer or second active material layer is applicable.
[0084] (positive electrode)
[0085] The positive electrode includes, for example, a positive electrode current collector and a positive electrode active material layer fixed on the positive electrode current collector. As the positive electrode current collector, a conductive member composed of a metal with good conductivity (such as aluminum) is suitable. As the positive electrode active material layer, for example, the first active material layer or the second active material layer described above is applicable.
[0086] (Diaphragm)
[0087] The diaphragm (separator) is an electrically insulating porous film. The diaphragm electrically isolates the positive electrode from the negative electrode. The diaphragm may have a thickness of, for example, 5 to 30 μm. The diaphragm may be composed of, for example, a porous polyethylene (PE) film, a porous polypropylene (PP) film, and the like. The diaphragm may have a multilayer structure. For example, the diaphragm may be composed by stacking a porous PP film, a porous PE film, and a porous PP film in sequence. The diaphragm may have a heat-resistant layer on its surface. The heat-resistant layer contains a heat-resistant material. Examples of heat-resistant materials include metal oxide particles such as aluminum oxide, high melting point resins such as polyimide, and the like.
[0088] (use)
[0089] Examples of uses of the battery include power sources for hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV), and battery electric vehicles (BEV).
[0090] Example
[0091] The present disclosure will be described below based on examples, but the present disclosure is not limited to these examples. It should be noted that in the following description, "parts" and "%" are all based on mass unless otherwise specified.
[0092] <Examples 1 to 4, Comparative Examples 1 and 2>
[0093] In each of the Examples and Comparative Examples, the active material layer having the following composition was irradiated with the laser light while adjusting the output power and overlap ratio of the irradiated nanosecond pulse laser as shown in Table 1 to change the input heat.
[0094] (irradiation conditions)
[0095] Laser pulse width: 50ns, output power: 2.5W~5W, overlap rate: 0%~63%
[0096] Active material layer composition: negative electrode active material = graphite, binder = styrene butadiene copolymer (SBR), thickener = carboxymethyl cellulose (CMC), conductive material: carbon nanotube (CNT)
[0097]
Table 1
[0098]
[0099] <Evaluation>
[0100] (1) Quality loss
[0101] In each of the Examples and Comparative Examples, the change in mass (mass loss (%)) of the active material layer was measured before and after nanosecond pulse laser irradiation. The results are plotted as a graph. Figure 1 .
[0102] like Figure 1 As shown in the coordinate diagram, in Example 1 (heat input 0.005J / mm 2 )、Example 2(0.01J / mm 2 )、Example 3(0.022J / mm 2 ) and Example 4 (and 0.04 J / mm 2 ) the mass loss of the active material layer was suppressed to less than 6%, while in Comparative Example 1 (heat input 0.06 J / mm 2 ) and Comparative Example 2 (0.08 J / mm 2 ) the mass loss of the active material layer significantly exceeded 6%.
[0103] (2) Battery resistance
[0104] Using the active material layers of Example 1 and Example 2 with less mass loss, a battery was produced and a battery resistance test was conducted. In addition, as a reference example (Reference: Ref), a battery resistance test was also conducted in the same manner for an active material layer whose surface was not irradiated with nanosecond pulse laser. The evaluation results are plotted as a graph of the ratio (%) to the reference example (Ref). Figure 2 .
[0105] The battery used in the battery resistance test had a laminated cell structure (positive electrode 45 mm×47 mm, negative electrode 47 mm×49 mm).
[0106] like Figure 2 As shown in the coordinate graph, it can be seen that in Example 1 and Example 2, the battery resistance can be reduced compared to the reference example (Ref).
[0107] (3) Average particle size of the binder
[0108] For Example 1 and the reference example (Reference: Ref), the average particle size of the binder in the surface image obtained by EPMA mapping in which the binder was dyed was measured.
[0109] The active material layers of Example 1 and Reference Example were stained with osmium (Os), and EPMA (Electron Probe Micro Analysis) mapping images were obtained for the surfaces of the active material layers after staining.
[0110] The top 10% of the brightness data with the highest brightness was calculated from the mapped image, and the brightness data was set as the threshold value, and binarization was performed. The particle size (length of the longest part) of the binder (SBR) particles was measured for 20 binder particles from the binarized image, and the arithmetic mean was taken as the average particle size. The results are shown below.
[0111] -Average particle size-
[0112] Example 1: 35 μm
[0113] Reference example (Ref): 17μm.
Claims
1. A method for producing an active material layer for a battery, comprising: a step of preparing an active material layer including a binder and an active material; and The active material layer is heated to 0.005 J / mm 2 Above and 0.050J / mm 2 The irradiation step of nanosecond pulse laser was performed under the following conditions.
2. The method for producing an active material layer for a battery according to claim 1, wherein: The irradiation step is a step of irradiating with nanosecond pulse laser light under the conditions of an output of 1.25 W to 5 W and an overlap rate of 0% to 63%.
3. A battery active material layer comprising a binder and an active material, wherein the average particle size of the binder in a surface image based on EPMA mapping obtained by dyeing the binder is larger than the average particle size of the binder in an image of a cross section at a depth of 20 μm based on EPMA mapping.
4. A battery active material layer comprising a binder and an active material, wherein an average particle size of the binder in a surface image obtained by dyeing the binder and based on EPMA mapping is 30 μm or more. 5 . A battery comprising the battery active material layer according to claim 3 or 4 as at least one of a positive electrode active material layer and a negative electrode active material layer.
Citation Information
Patent Citations
Nonaqueous electrolyte battery
JP2011171020A